Organizational Communication Mini Audit at Senior High School During Pandemic: Audit Mini Komunikasi Organisasi di Sekolah Menengah Kejuruhan pada Masa Pandemi - Wahyudiono, Muhammad Arief; Rochmaniah, Ainur (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to determine the results of the audit at SMKN 2 Buduran Sidoarjo Pada, especially the communication carried out within the organization through technology such as Whatsapp and this study aims to evaluate what obstacles occur during communication at SMKN 2 Buduran Sidoarjo. This method uses a quantitative descriptive method. The population and sample in this study were all employees who worked at SMKN 2 Buduran Sidoarjo with a sample of 83 respondents, the data collection process used a questionnaire. In the research, the results were quite good from the management aspect, organizational aspect, communication aspect, and feedback aspect.